A study of metastatic lesions of lymph nodes by fine needle aspiration cytology - Meena, Pratibha; Mishra, Ranu Tiwari (International Journal of Research in Medical Sciences, 2017)
Background: FNAC is rapidly emerging as a useful tool in the diagnosis of metastatic lesion of lymph nodes. FNAC not only confirms or excludes metastasis in a case of a known primary malignancy but, also, in most cases helps to detect occult primary malignancy. Aim of present study was to determine the frequency of metastatic lesions of lymph nodes. Methods: This retrospective study was done of all metastatic lymph node lesions reported on FNAC, in the department of pathology, NSCB medical college, Jabalpur from January 2014 to December 2014 (One Year). Results: Total cases of 400 lymph node aspiration were done, of which 120 cases were clinically suspicious of metastasis. Cytology results were positive for metastasis in 97 cases (80.8%). The most common site of aspiration was cervical lymph nodes (75.2%). Maximum number of cases of metastasis were in 51-60 years age group with male predominance (male:female 2.6:1). The most common metastasis was squamous cell carcinoma seen in 74 cases (76.2%), followed by metastatic mammary carcinoma (10.3%), remaining were adenocarcinoma, undifferentiated carcinoma, malignant melanoma, papillary thyroid carcinoma and transitional cell carcinoma. Conclusions: FNAC is a rapid, safe and cost-effective technique. It gives early and accurate results with minimal invasion and reduces the need for surgical biopsies, thus saves cost and time to reach the final diagnosis. It is therefore concluded that FNAC is a useful tool in diagnosing metastatic lesions of lymph nodes with a good certainty.